Penerapan Model Make A Match Untuk Meningkatkan Hasil Belajar Pai Materi Asmaul Husna Siswa Kelas IV - Muhamad Rif'an; Rohma Yunita; Imam Fauzi (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
This study was motivated by the low learning outcomes in Islamic Religious Education (PAI) on the topic of Asmaul Husna among fourth-grade students of SDN 13 Way Khilau, which was caused by teacher-centered learning. This study aims to improve learning outcomes in PAI on the topic of Asmaul Husna through the application of the Make a Match learning model. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 25 fourth-grade students. Data were collected through tests, observation, and documentation, then analyzed using quantitative and qualitative descriptive techniques. The results show an increase in classical completeness from 40% in the pre-cycle to 64% in cycle I and 88% in cycle II, accompanied by an increase in student activeness. Thus, the application of the Make a Match model can improve PAI learning outcomes on Asmaul Husna for fourth-grade students of SDN 13 Way Khilau.